Effects of task-oriented training on upper extremity function and performance of daily activities by chronic stroke patients - Park, JuHyung; Yoo, Chanuk (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of this study was to determine the effects that task-oriented training has on upper extremity function and performance of daily activities by chronic stroke patients. [Subjects and Methods] Task-oriented training was applied to two chronic hemiplegic patients in this research. The training was provided to each patient for 30 minutes a day, five times a week for two weeks. The treatment program included six different types of training that could be performed by the patients themselves. Evaluation was performed four times, that is, once a week for three weeks before the intervention and once after the intervention. The change in upper extremity function was measured with the Manual Function Test, and the change in performance of daily activity was measured with the Functional Independence Measure. [Results] The upper extremity function of both subjects was improved after application of task-oriented training. However, in the performance of daily activities, subject one showed improvement compared to with before the intervention, whereas subject two showed the same results. [Conclusion] This research confirmed that two weeks of task-oriented training for chronic stroke patients is effective for improvement of upper extremity function and performance of daily activities by chronic stroke patients.